Unveiling the antibacterial potential of latex-derived phytocomponents from Calotropis gigantea targeting bacterial Penicillin-binding proteins: chemical profiling, in silico docking, and in vitro lab validation - Arun Sharma; Amrita Chauhan (Acta Biologica Slovenica)
Uncontrolled use of currently accessible medicines has caused antibiotic resistance in bacteria worldwide. This work aimed to undertake molecular docking and chemical profiling of bioactive components extracted from Calotropis gigantea latex, with wet lab confirmation to follow. Gas chromatography was used to analyze the phytochemical profile. The docking tool, Cb-dock2, was used for in-silico analysis. G+ and G- bacterial strains were utilized to confirm the wet lab results. Chemical profiling revealed 18 peaks, and some major bioactive compounds were like phytol, 4-methyl-2- phenylindole and α-tocospiro A. Docking analysis revealed strong interaction against bacterial Penicillin-binding Protein (PBP1a) with docking scores ranging from -5.2 to -7.9 (Vina score). The PBP-Ligand complex has Van der Waals, hydrogen bond, pi-cation, and alkyl bonding interactions, according to the results of the interaction investigations. Calotropis latex successfully suppressed the development of bacterial strains (G+ and G-) with inhibition zones ranging from 1.1 cm to 2.2 cm, as demonstrated by in-vitro tests, indicating their potential as antibacterial medications. The study found that latex-based bioactive compounds have the potential to be used in the pharmaceutical and biotechnology sectors by facilitating the creation of structural alterations that lead to stronger medications. Therefore, this latex-derived compound may open a new pipeline into the development of multi-target antibiotics against a broad-spectrum multidrug-resistant G- bacterium.